2015
DOI: 10.1002/joc.4374
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐decadal assessment of the performance of gauge‐ and model‐based rainfall products over Saudi Arabia: climatology, anomalies and trends

Abstract: CitationEl 15indicate that the gauge-based products were generally skillful in reproducing rainfall characteristics in Saudi Arabia. In most cases, the 16 gauge-based products were also able to capture the annual cycle, anomalies and climatologies of observed data, although significant 17 inter-product variability was observed, depending on the assessment metric being used. In comparison, the GCM-based products 18 generally exhibited poor performance, with larger biases and very weak correlations, particularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 44 publications
2
62
0
Order By: Relevance
“…These findings were also consistent with the results of IPCC (). This study, as the first attempt to investigate the modified Thornthwaite climate categories based on ground‐based observations over Southwest Asia, indicated that the hot‐arid climate (34.5%) was predominant during the current period of 1971–2015, and the warm‐arid (21.7%) and torrid‐arid (13.8%) climates were in the next orders, respectively. In this context, it is important to mention that the previous attempts for producing the global map of the modified Thornthwaite climate classification (e.g., by Elguindi et al (, )) were based on global climate datasets (e.g., the University of Delaware dataset [UDel]) which does not have a proper accuracy for characterizing the monthly precipitation and temperature across the study region (Azizi et al, ; El Kenawy and McCabe, ). Based on the modified Thornthwaite climate classification system, which considers both thermal and moisture conditions for vast areas of Southwest Asia, changes in annual temperature (and consequently evapotranspiration) plays a more important role than precipitation does in terms of the alteration in climate. Changes in the modified Thornthwaite's thermal and moisture indices, as a result of climatic change associated with RCP4.5 and RCP8.5 scenarios predicted by the 17 GCMs, suggest a general drying and warming trend within most of Southwest Asia. More precisely, the moisture index is expected to decrease on average by 0.06 for the period 2071–2100 under the RCP8.5 scenario.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were also consistent with the results of IPCC (). This study, as the first attempt to investigate the modified Thornthwaite climate categories based on ground‐based observations over Southwest Asia, indicated that the hot‐arid climate (34.5%) was predominant during the current period of 1971–2015, and the warm‐arid (21.7%) and torrid‐arid (13.8%) climates were in the next orders, respectively. In this context, it is important to mention that the previous attempts for producing the global map of the modified Thornthwaite climate classification (e.g., by Elguindi et al (, )) were based on global climate datasets (e.g., the University of Delaware dataset [UDel]) which does not have a proper accuracy for characterizing the monthly precipitation and temperature across the study region (Azizi et al, ; El Kenawy and McCabe, ). Based on the modified Thornthwaite climate classification system, which considers both thermal and moisture conditions for vast areas of Southwest Asia, changes in annual temperature (and consequently evapotranspiration) plays a more important role than precipitation does in terms of the alteration in climate. Changes in the modified Thornthwaite's thermal and moisture indices, as a result of climatic change associated with RCP4.5 and RCP8.5 scenarios predicted by the 17 GCMs, suggest a general drying and warming trend within most of Southwest Asia. More precisely, the moisture index is expected to decrease on average by 0.06 for the period 2071–2100 under the RCP8.5 scenario.…”
Section: Discussionmentioning
confidence: 99%
“…This dataset was compiled from monthly rainfall observations at meteorological stations across the global land areas, providing anomalies from a 1961 to 1990 mean and allowing absolute monthly values to be obtained when combined with the climatology (Harris et al, 2014). CRU data (v3.22) have been validated against in situ observations in many regions worldwide, confirming their reliability (e.g., El Kenawy and McCabe, 2015;Livneh et al, 2015;Stagge et al, 2015). Accordingly, this dataset can provide valuable information on relatively reasonable spatial and temporal resolutions for assessment of current droughts and their impacts in the region.…”
Section: Datamentioning
confidence: 95%
“…Unfortunately, the Middle East region in general suffers from a paucity of gauge observations in both space and time, which is a prerequisite for any reliable assessment of this high regional climate variability. Besides the political and socioeconomic instability of many countries in this region, the lack of gauge density is associated with poor sitting of instrumentation, the high cost of equipment installation, a record of poor maintenance, and the vast unpopulated areas across characteristic of the region (El Kenawy and McCabe, ; Gunkel and Lange, ). Overall, the countries of the Middle East share common challenges, as gauged data either have a sparse spatial distribution, cover a short time interval, suffer from gaps and discontinuities, or have a coarse temporal reporting resolution (monthly or longer).…”
Section: Introductionmentioning
confidence: 99%